Proposal for housing with bioclimatic criteria and low cost - Dick Zambrano, Santiago Raymundo; Coque Arias, Jorge; Oviedo Machuca, Carlos (Revista Universidad de Guayaquil, 2017)
This dissertation aims to analize with DesignBuilder Simulation, the thermal properties of housing with bioclimatic and low-cost criteria. In addition, it proposes a model of low-cost, one-storey house employing bioclimatic criteria and materials from the medium, improving hygrothermal comfort and habitability conditions. The building technology used, prioritizes the favorable comfort conditions, regarding its cost. Under such criterion, the material for each envelope element is sized and classified, considering a relationship of cost-benefit and reality. Representative elements from the coastal and traditional architecture are taken into account for the housing project. For the temperature ranges, those established in the Fanger Diagram from the Ecuadorian Standard “Normas Ecuatorianas de Construcción 2011, Chapter 13, Eficiencia Energética en la Construcción en Ecuador” were considered, according to the thermal simulation results modeled with the DesingBuilder software. Different materials and dimensions were modeled with a cost-benefit relationship, setting a housing model in which the inside temperature surpasses the comfort line when the outdoor temperature is above 31°C.
Keywords: building; housing; bioclimatic criteria; low-cost; hygrothermal comfort; habitability